2024
DOI: 10.3390/cancers16020318
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Esophageal Cancer Treatment: Immunotherapy in Neoadjuvant and Adjuvant Settings

Daniel Park,
Won Jin Jeon,
Chieh Yang
et al.

Abstract: Locally advanced esophageal cancer (LAEC) poses a significant and persistent challenge in terms of effective treatment. Traditionally, the primary strategy for managing LAEC has involved concurrent neoadjuvant chemoradiation followed by surgery. However, achieving a pathologic complete response (pCR) has proven to be inconsistent, and despite treatment, roughly half of patients experience locoregional recurrence or metastasis. Consequently, there has been a paradigm shift towards exploring the potential of imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…MSI-H tumors are known to have a better response [19] when treated with immune checkpoint inhibitors; this might explain part of the achievement of a high pathCR rate in the PANDA trial. That cohort was also favored by the 90% prevalence of patients with a positive PD-L1 result (CPS ≥ 1), thus responding very well to the PD-L1 inhibitor [20], while 35% of our cohort (n = 7/20 patients) had a positive PD-L1 result. A larger randomized controlled clinical trial is necessary to not only reduce biases but to warrant validation of these observed results.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…MSI-H tumors are known to have a better response [19] when treated with immune checkpoint inhibitors; this might explain part of the achievement of a high pathCR rate in the PANDA trial. That cohort was also favored by the 90% prevalence of patients with a positive PD-L1 result (CPS ≥ 1), thus responding very well to the PD-L1 inhibitor [20], while 35% of our cohort (n = 7/20 patients) had a positive PD-L1 result. A larger randomized controlled clinical trial is necessary to not only reduce biases but to warrant validation of these observed results.…”
Section: Discussionmentioning
confidence: 77%
“…Immune checkpoint inhibitors have been found to improve OS when added to frontline chemotherapy in patients with advanced esophageal, GEJ, and gastric cancer [20,[23][24][25]. However, the current results from other trials incorporating ICIs in the localized setting, namely Attraction-5 [26] (post-operative approach but relevant to occult disease) and Keynote-585 [27], are mostly not superior.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation